An Engel condition with generalized skew derivations on multilinear polynomials. Issue 10 (3rd October 2018) - Albaş, E.; Argaç, N.; De Filippis, V.; Demir, Ç.
ABSTRACT: Let R be a prime ring of characteristic different from 2 with right Martindale quotient ring Q and extended centroid C . Let further be a fixed integer, a multilinear polynomial over C which is not central-valued on R . If is a nonzero generalized skew derivation of R such that for all, then either there exists such that for all, or one of the following holds: (a) and is central-valued on R for a suitable ; (b) there exist with such that for all, and is central-valued on R .